2018
DOI: 10.1002/pssr.201800464
|View full text |Cite
|
Sign up to set email alerts
|

Plasmonic Helicity‐Driven Detector of Terahertz Radiation

Abstract: A theory of the helicity‐driven plasmonic dc response of a gated two‐dimensional electron gas to terahertz (THz) radiation is developed. A general diagram of a plasmonic detector operating in different regimes is found and analytical equations describing all these regimes are derived. It is demonstrated that the helicity‐sensitive part of the response dramatically increases in the vicinity of the plasmonic resonances and oscillates with the phase shift between the excitation signals on the source and drain. Th… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 56 publications
(221 reference statements)
0
7
0
Order By: Relevance
“…To enhance the quantum efficiency of the THz photoconductive antenna, and hence the photon density of the THz beam, innovative architectures to improve the design of the photoconductive antennas were proposed and fabricated. 157,159 In the following sections, some of these devices are reviewed.…”
Section: Advances In Terms Of Terahertz Devicesmentioning
confidence: 99%
“…To enhance the quantum efficiency of the THz photoconductive antenna, and hence the photon density of the THz beam, innovative architectures to improve the design of the photoconductive antennas were proposed and fabricated. 157,159 In the following sections, some of these devices are reviewed.…”
Section: Advances In Terms Of Terahertz Devicesmentioning
confidence: 99%
“…(3)(4)(5) with the boundary conditions given by Eq. (2) is obtained using the same approach as in [2,12] ω ω γ ω ω γ ω ω…”
Section: Terafet Spectrometer Principle Of Operationmentioning
confidence: 99%
“…This situation can be modeled by the following boundary conditions (see These equations can be rewritten in a form used in Ref. [12] (0) cos t,…”
Section: Homodyne Detector Operation Schemementioning
confidence: 99%
See 1 more Smart Citation
“…The plasma wave velocity in 2D materials is normally an order of magnitude larger than the electron drift velocity and is much smaller than the speed of light. Hence, the plasmonic submicron-sized interferometers based on 2D materials are expected to operate efficiently in the terahertz (THz) frequency range. , In particular, it has been predicted theoretically that a field-effect transistor (FET) can serve as a simple device for studying plasmonic interference effects. Specifically, it was suggested that an FET with two antennas attached to the drain and source shows a dc current response to circularly polarized THz radiation which is partially driven by the interference of plasma waves and by helicity of incoming radiation. The first experimental hint on the existence of such an interference contribution was reported in ref for an industrial FET, where helicity-driven effects were obtained due to unintentional peculiarities of contact pads.…”
Section: Introductionmentioning
confidence: 99%